The Impact of Corruption on the Institutions of Political Power in the Republic of Kazakhstan: The Cratological Context and Law Enforcement Activities - SALKEBAYEV, Talgat Smagulovich (Journal of Advanced Research in Law and Economics, 2017)
Since the Republic of Kazakhstan gained its sovereignty in the law enforcement system, a number of large-scale reforms have been carried out, state programs have been approved and implemented, a full-scale recertification of employees of all law enforcement agencies, and a regulatory base have been updated through the adoption of special laws on law enforcement and internal affairs bodies. However, despite all the above circumstances, the level of corruption in the internal affairs bodies is still high. Obviously, there is a whole complex of latent reasons for this situation and the author denotes the contours of their scientific research. The most difficult direction, which the author singled out, should be recognized as a change in approaches to the formation of a strategy for combating corruption. This article suggests a preliminary analytical description of the impact of corruption on political institutions in terms of cratology and the most significant aspects of regulation.